PENGARUH AKREDITASI DAN REPUTASI TERHADAP MINAT CALON MAHASISWA (STUDI PADA PTKIN SE-INDONESIA) - Nalim, Nalim; Afiani, Lia; Zahro, Fatimatuz; Safitriani, Eka (Jurnal Penjaminan Mutu, 2025)
This study aims to analyze the effect of higher education accreditation ratings and the influence of university reputation on the number of applicants/enthusiasts. This research is a quantitative research with data collection techniques in the form of observation and documentation. The population in this study were 57 PTKINs spread throughout Indonesia. The sampling technique in this study used saturated sampling, where all members of the population were sampled. The data analysis technique used is multiple regression analysis using SPSS software. The results of the study show that there is a significant effect of higher education accreditation ranking on the number of applicants, while the reputation of the tertiary institution has no effect on the number of applicants. However, simultaneously the variables of higher education accreditation rating and university reputation have a significant effect on the interest of prospective students.